Pemberdayaan Perempuan Melalui Majelis Taklim Dar El Ihsan: Studi Penguatan Solidaritas Sosial Ibu-Ibu di Bambu Apus Pamulang - Kurniawati Rahmah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Majelis Taklim (Islamic study groups) in urban areas play a strategic role beyond traditional religious education, specifically as a means of empowering women's social movements. This study aims to analyze the mechanisms of women's empowerment through Majelis Taklim Dar El Ihsan and its impact on strengthening social solidarity in Bambu Apus Village, Pamulang. Using a qualitative approach with a case study design, primary data were collected through in-depth interviews with administrators and congregants, supported by participant observation and documentation studies. The results indicate that Majelis Taklim Dar El Ihsan implements an empowerment model by integrating religious material with practical guidance, such as on family management and microeconomic empowerment. The resulting social solidarity is manifested in emotional and material support (bonding social capital) and social inclusiveness (bridging social capital), which bridges interactions between existing residents and newcomers. These findings confirm that Majelis Taklim effectively functions as a "third space" in building social resilience in urban communities through empowering women's institutions.